Hazardous volatile organic compounds in ambient air of China. (May 2020) - Lyu, Xiaopu; Guo, Hai; Wang, Yu; Zhang, Fan; Nie, Kun; Dang, Juan; Liang, Zhirong; Dong, Shuhao; Zeren, Yangzong; Zhou, Beining; Gao, Wei; Zhao, Shizhen; et al.
Abstract: Volatile organic compounds (VOCs) are ubiquitous in the atmosphere and the majority of them have been proved to be detrimental to human health. The hazardous VOCs were studied very insufficiently in China, despite the enormous emissions of VOCs. In this study, the concentrations and sources of 17 hazardous VOCs reported in literature were reviewed, based on which the health effects were assessed. In-depth survey indicated that benzene and toluene had the highest concentrations in eastern China (confined to the study regions reviewed, same for the other geographic generalization), which however showed significant declines. The southern China featured high levels of trichloroethylene. Dichloromethane and chloroform were observed to be concentrated in northern China. The distributions of 1, 2-dichloropropane and tetrachloroethylene were homogeneous across the country. Basically consistent with the spatial patterns of ozone, the summertime formaldehyde exhibited higher levels in eastern and northern China, and increased continuously. While transportation served as the largest source of benzene and toluene, industrial emissions and secondary formation were the predominant contributors of halogenated hydrocarbons and aldehydes (formaldehyde and acetaldehyde), respectively. The chronic non-cancer effects of inhalation exposure to the hazardous VOCs were insignificant, however the probabilities of developing cancers by inhaling the hazardous VOCs in ambient air of China were quite high. Formaldehyde was identified as the primary carcinogenic VOC in the atmosphere of most regions. The striking results, especially the high inhalation cancer risks, alerted us that the emission controls of hazardous VOCs were urgent in China, which must be grounded upon full understanding of their occurrence, presence and health effects. Highlights: First review specifically focusing on occurrences and health risks of hazardous VOCs in China. Most hazardous VOCs present higher concentrations in China than in developed countries. Traffics and industrial emissions dominate sources of aromatics and halogenated hydrocarbons, respectively. Formaldehyde imposes highest inhalation cancer risk, and the situation is getting worse.